Sistem Informasi Monitoring Proyek dan Aktivitas Harian Pada PT. Visio Indonesia - Agung Dewantoko; Andiani (Teknik Informatika Universitas Pancasila, 2023)
Project Monitoring Information System of PT. Visio Informatika built to support project execution both external and internal project in PT. Visio Informatika. System constructed using the programming language PHP (Hypertext Prepocessor) version 5 and Laravel Framework and MySQL database.This web-based informatin system can help the Project Manager monitor the progress of the project and be an effective communication for all member of project. So that project implementation can monitored and give the best result.